Combined Efficacy of Adrenal Vein Sampling and Imaging Findings in Predicting Clinical Outcomes Following Unilateral Adrenalectomy for Primary Aldosteronism - Rajiv N. Srinivasa; Matthew E. Anderson; Alan P. Dackiw; Anil K. Pillai; Clayton K. Trimmer; Sanjeeva P. Kalva; Stephen P. Reis (Journal of Clinical Interventional Radiology ISVIR, 2017)
The objective of this study was to investigate the combined efficacy of adrenal vein sampling (AVS) and imaging findings in predicting successful clinical outcomes following unilateral adrenalectomy for primary aldosteronism (PA). A retrospective chart review of 137 patients who underwent AVS between 2009 and 2014 at two hospitals in a single academic institution was performed. Preprocedure demographic, imaging, medication, and laboratory values were reviewed. In general, patients were considered for adrenalectomy when lateralization was suggested on AVS. Clinical outcomes such as improved blood pressure control and preserved renal function after adrenalectomy were correlated with preprocedure variables. AVS was technically successful in 120 out of 137 patients. Lateralization was seen in 64 patients and 48 out of 64 patients underwent adrenalectomy. Out of 48, 43 patients had an adrenal nodule on preoperative imaging, while 5 did not. 28 patients showed improvement in blood pressure after adrenalectomy, all of which had a nodule on imaging. Of the 28 patients, 22 also showed preservation of renal function. None of the remaining 5 (out of 48) patients who demonstrated lateralization on AVS and had no nodule on imaging showed clinical improvement following adrenalectomy. The presence of an adrenal nodule on preoperative imaging was also associated with improved blood pressure control (p = 0.022) and preserved renal function (p = 0.048) following adrenalectomy. Improved blood pressure control and preserved renal function in patients with PA who underwent adrenalectomy following lateralization on AVS are associated with the identification of an adrenal nodule on preoperative imaging.